Strategi Industrialisasi Pengembagan Industri Kreatif Melalui E-Commmerce di Kota Batu - Franciska Christiana; Nur Fakhri Febriansyah; Muhammad Yasin (Student Research Journal, 2023)
This research aims to understand, describe, analyze the development process and innovation strategies as well as factors that influence the creative industry in Batu City. This research uses qualitative research methods. Data processing is done with reasoning and mindset that behaves and acts based on logic. This analysis goes through several stages, namely data reduction, data presentation, and conclusion drawing. The results showed that: (1) The development of the creative industry in Batu City is very influential on the creativity and innovation of business people. (2) There are factors that influence the development of the creative industry in Batu City. (3) Development and innovation strategies for the creative industry through e-commerce in order to remain competitive in the era of globalization.